Socialization of Legal Understanding towards Street Merchants (PKL) who Provide Trading in Locations that are Prohibited from A Progressive Law Enforcement Perspective - Mia Putri Indriyanty; Taufiq Nugroho (Universitas Muhammadiyah Surakarta, 2023)
Cases of murder of children by biological mothers in Indonesia still occur frequently and are in the public spotlight. In the case study of Decision Number 333/PID.SUS/2021/PN BKS, a biological mother was charged with the murder of her own biological child who was only 9 months old. In the indictment, the public prosecutor used Article 75 paragraph (2) of the Republic of Indonesia Law Number 36 of 2009 concerning Health as a legal basis for charging the perpetrators. The article states that anyone who violates health provisions that causes the death of another person can be charged with imprisonment. In terms of juridical payments, Article 75 paragraph (2) of the Republic of Indonesia Law Number 36 of 2009 concerning Health is indeed relevant to the case of child murder by the biological mother. However, in this case, there were several weaknesses in the public prosecutor's indictment. First, there is no medical evidence indicating that the child's health was seriously impaired due to the mother's violent or negligent actions. Second, there is no strong evidence that the mother's violent actions or actions were detrimental to killing her child. In an effort to prevent cases of killing children by biological mothers in the future, the government also needs to increase public awareness about the importance of child health and protection. Education on how to care for children properly and how to deal with stress in pregnant women or mothers with young children also needs to be improved. In addition, the government also needs to strengthen supervision of acts of violence or negligence against children to prevent cases of homicide by parents or guardians that harm the health and life of children.